Texture, Color, Vitamin C and Reducing Sugar Content of Milk Toffee Added with Dracaena angustifolia Leaves Aqueous Extract as Natural Colorant - Herly Evanuarini; Dicky Tri Utama; Firman Jaya (Faculty of Animal Science Universitas Brawijaya, 2020)
The leaf of Dracaena angustifolia has been used widely not only as natural food colorant but also as a natural source of vitamin C. The objective of this study was to obtain the best addition level of Dracaena angustifolia leaves aqueous extract as natural food colorant for milk toffee based on its effect on texture, color, vitamin C and reducing sugar content. Milk toffee was formulated with different addition levels of Dracaena angustifolia leaves aqueous extract as treatment; 3%, 4%, 5%, 6% on weight/milk volume basis, and compared to control (0%). Higher addition level of Dracaena angustifolia leaves aqueous extract to milk toffee resulted in higher (P<0.01) L*, a*, b* values, and softer texture. Vitamin C and reducing sugar content were increased by the addition of 4% extract. However, there were no further differences on vitamin C and reducing sugar content when the addition level was increased up to 6%. Therefore, among treatments, the highest addition level used in this study (6%) is suggested as the best addition level according to texture, color, vitamin C content and reducing sugar content of milk toffee. The addition of natural food colorant, which contains antioxidant, e.g. Dracaena angustifolia leaves aqueous extract, also promotes the diversification of milk toffee.